2022
DOI: 10.1093/ecco-jcc/jjac080
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and tolerability of oral sulphate tablet for bowel preparation in patients with inflammatory bowel disease: A multicentre randomized controlled study

Abstract: Background and Aims We evaluated the efficacy, safety and tolerability of novel oral sulphate tablets [OSTs] vs 2 L of polyethylene glycol and ascorbate [PEG/Asc] in patients with inflammatory bowel disease [IBD]. Patients and Methods A total of 110 patients with clinically inactive IBD were enrolled in this single-blind multicentre non-inferiority study. Patients were randomly assigned to the OST or 2 L PEG/Asc group and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although tablets are relatively easy to administer, children often complain of difficulty taking pills. In this study, the complete ingestion rate of the OST group was 87.1%, whereas that of adults in the OST group was 100% in a previous study (16). In addition, all patients in our study underwent bowel preparation and colonoscopy during hospitalization, which leads to problems such as school absences in school-age patients.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Although tablets are relatively easy to administer, children often complain of difficulty taking pills. In this study, the complete ingestion rate of the OST group was 87.1%, whereas that of adults in the OST group was 100% in a previous study (16). In addition, all patients in our study underwent bowel preparation and colonoscopy during hospitalization, which leads to problems such as school absences in school-age patients.…”
Section: Discussionmentioning
confidence: 56%
“…When the administration of a previously approved bowel preparation regimen is challenging, OST is considered a secondary option based on the voluntary intention of patients and guardians. In studies involving adults, the use of OST for bowel preparation was not inferior in efficacy and was safe and well tolerated (15)(16)(17).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a subsequent trial targeting patients with inactive IBD, Kim et al [ 19 ] reported a lower bubble score rate in the novel oral sulphate table preparations and higher palatability (including a willingness to reuse the preparation for subsequent colonoscopy) than the PEG-ascorbate comparison. The problem of bubbles is another technical aspect to consider when discussing mucosal visibility, so much so that the use of simethicone for this purpose is bleached out by European guidelines and also found beneficial for IBD[ 5 , 8 ].…”
Section: What Profile Do Non-peg Solutions Have In Ibd?mentioning
confidence: 99%